Public Trust Matters: The Role Of DPRD Seluma Public Relations In Enhancing Public Trust Through Instagram - Yeyen Indriasari; Dilmai Putra; Maryaningsih Maryaningsih (Journal of Law, Social Science, and Management Review, 2026)
This study examines the role of public relations of the Seluma Regency Regional House of Representatives in increasing public trust through digital communication on the institution’s Instagram account. The development of digital media has transformed communication patterns between public institutions and society, making information transparency, responsiveness, communication consistency, and public involvement important factors in building public trust in government institutions. The purpose of this research is to analyze how the public relations unit of the Seluma Regency Regional House of Representatives manages digital communication through Instagram in order to enhance public trust. This research uses a qualitative approach with a descriptive method. Data were collected through interviews with public relations officers and social media administrators, observation of digital communication activities on the institution’s Instagram account, and supporting documentation related to public communication activities. The findings show that the Instagram account of the Seluma Regency Regional House of Representatives functions as a medium for basic information transparency by publishing institutional activities such as meetings, working visits, and other official agendas. However, the transparency presented is still dominated by visual documentation and does not provide sufficient substantive information regarding the results of activities or policy decisions. Responsiveness to public questions and comments remains limited, causing digital communication to operate mostly in a one way pattern. Although posting activities appear relatively consistent, the accountability of information is not yet fully developed because the content emphasizes activity documentation rather than the explanation of institutional performance outcomes. In addition, public involvement remains low because interactions from citizens are rarely followed by visible responses or follow up from the institutio.